MEFORMAS1 YEND1I)IMAN UNTUK MENGURANGB PEMIEAKU ANARK1 DAN MENIJ,JIJ MASYARAK.41' MADANI - Siii Irene Astuti I) Siii Irene Astuti I) (Jurnal Cakrawala Pendidikan, 1999)
I he acts of anarchy occurring in social life may hecaused by the unslrccessful implementation of the nationaleducational system in the course of shaping society membersinto cultured and dignified individuals who live well.What has been wrong in thc government'sapplication of the national educational system has been theutilization of education as a tool to maintain authority ratherthan an effort of humanizing man. In so doing the nationaleducational system has also eliminated the individualti-eedom of expression and creativity.A reformation of the national education for thepurpose of supporting the formation of a civil society is Ili~1.ciiii.c0 f'~i~nic~l~~llp 0i.i;liici iei iic ~ aI ! otii I ilc i':Itb~:!-ii.,:l;ii I-cii~riliaiisra: gci~dac all I);. .,i~cci..;s:iiio iii). il'i,hciiare ittiel-~elaliona mong ant! cvillingrtes.s of al! p:irtiesii-ivo1ci.d i r i the process of ilidividi!;ri aild comrnxnityetfticatiain i r n llrc course of fcxrrrra~g :i society of culturedunil dignified persons who uphold dcrnocraiic values Imighiyi l r isnilding a peaceti! and pl-ospel-ous society.